2018
DOI: 10.1007/s12028-018-0526-8
|View full text |Cite
|
Sign up to set email alerts
|

Midline Shift is Unrelated to Subjective Pupillary Reactivity Assessment on Admission in Moderate and Severe Traumatic Brain Injury

Abstract: BackgroundThis study aims to determine the relationship between pupillary reactivity, midline shift and basal cistern effacement on brain computed tomography (CT) in moderate-to-severe traumatic brain injury (TBI). All are important diagnostic and prognostic measures, but their relationship is unclear.MethodsA total of 204 patients with moderate-to-severe TBI, documented pupillary reactivity, and archived neuroimaging were included. Extent of midline shift and basal cistern effacement were extracted from admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Basal cistern effacement is closely associated with pupillary reactivity midline shift. Thus, it can represent a uniquely useful neuroimaging characteristic to guide intervention in TBI [ 32 ]. Our study focused on developing prognostic models of predicting the 1-year mortality of TBI patients undergoing DC.…”
Section: Discussionmentioning
confidence: 99%
“…Basal cistern effacement is closely associated with pupillary reactivity midline shift. Thus, it can represent a uniquely useful neuroimaging characteristic to guide intervention in TBI [ 32 ]. Our study focused on developing prognostic models of predicting the 1-year mortality of TBI patients undergoing DC.…”
Section: Discussionmentioning
confidence: 99%
“…Basal cistern effacement is closely associated with pupillary reactivity midline shift. Thus, it can represent a uniquely useful neuroimaging characteristic to guide intervention in TBI 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of Kouvarellis et al with 141 pediatric cases with traumatic brain injury, resulted in an increase in intracranial pressure in patients with close basal cistern and lower survival rates [23]. Nourallah et al revealed that evaluation of basal cisterns in brain CT was directly related to brain stem pressure independent of other parameters (such as age, midline sp shift) in assessing premorbid findings in traumatic brain injury [24].…”
Section: Discussionmentioning
confidence: 99%
“…Uncal, parahippocampal, and central transtentorial herniation reflect the pressure effects of a wider range of compartments, and basal cistern pressure can be detected earlier, radiologically [24]. In the literature, radiological signs have been tried to be defined as pre-herniation findings indicative of urgent decompressive craniectomy to help to diagnos and treat brain stem damage that will be developed secondary to malignant MCA infarction.…”
Section: Discussionmentioning
confidence: 99%